Islamic Financial Inclusion and Economic Growth: a case study in East Kalimantan - Rahmah, Fitria (Etihad: Journal of Islamic Banking and Finance, 2023)
Introduction: Stability in the financial system is a component that can stimulate economic expansion. However, this cannot be accomplished if only a minority of the population has access to the financial system's intermediation function. This may be due to a lack of access, information, or even public awareness of the use of financial services. The objective of this study is to ascertain the extent of inclusivity in East Kalimantan and examine how it influences the region's economic development. Therefore, financial inclusion plays a crucial role in fostering economic expansion by establishing stable financial conditions. Research Methods: The Vector Error Correction Model is applied to analyze data obtained from Sharia Banking Statistics (SPS OJK) and Central Statistics Agency (BPS) publications, in addition to other corroborating sources, for the purpose of this quantitative study. Results: The research findings indicate that the degree of Islamic financial inclusion in East Kalimantan was low in 2017 and 2018, but reached a high level in 2019, 2020, and 2021.   Conclusion: The immediate impact of Islamic financial inclusion on economic growth in East Kalimantan is substantial.   Nevertheless, over the 2017-2021 period, there is no substantial impact on the level of Islamic financial inclusion and economic growth in East Kalimantan in the long run.